Outcome and prognostic factors of interstitial lung disease patients with acute respiratory failure in the intensive care unit. (May 2020) - Lain, Wei-Ling; Chang, Shi-Chuan; Chen, Wei-Chih
Background: There are few studies reporting the clinical characteristics and outcomes of interstitial lung disease (ILD) patients with acute respiratory failure (ARF). The goal of this study is to investigate the clinical features, management, mortality, and associated factors in ILD patients with ARF requiring mechanical ventilation (MV). Methods: This was a retrospective, observational study conducted in a 24-bed intensive care unit (ICU) of a medical center in Taiwan during a 3-year period. Patients admitted to the ICU with a diagnosis of ILD with ARF needing MV were included for analysis. Patient characteristics, including demographics, critical-illness factors, and outcome data, were collected and analyzed. Results: A total of 82 patients with ILD who developed ARF were admitted to the ICU during the study period. At the onset of ARF, 38 patients received invasive MV, while 44 patients were treated with noninvasive MV. Overall in-hospital mortality was 65.9%, and 90-day and 1-year mortality were 69.5% and 76.8%, respectively. The independent risk factors for in-hospital mortality were worse oxygenation on days 5 and 7 after the onset of ARF. Invasive MV patients had significantly lower albumin levels, had higher Acute Physiology and Chronic Health Evaluation (APACHE) II scores at the onset of ARF, and received more vasopressors, sedatives, and corticosteroid pulse therapy during hospitalization compared with noninvasive MV patients. Conclusion: High in-hospital and long-term mortality rates were observed in ILD patients with ARF requiring MV. Poor oxygenation during hospitalization could serve as a predictive factor of poor prognosis. The reviews of this paper are available via the supplemental material section.